Surface Bending Resistance in Architected Nanoporous Metallic Materials. Issue 12 (3rd October 2022) - Zhang, Yongchao; Cai, Jun; Mi, Changwen; Akbarzadeh, Abdolhamid
Abstract: Finite element method (FEM) is considered as a powerful tool for predicting the mechanical behavior of complex structures. However, the commercially available numerical packages based on FEM are mainly limited to the evaluation of multiphysical properties at the continuum scale and are unable to accurately evaluate the response of nanomaterials since the dominant surface effects in nanoscale analysis are overlooked. In this study, our introduced numerical methodology not only incorporates the effects of surface residual stress and surface tensile stiffness based on the Gurtin–Murdoch surface elasticity but also takes into account the bending stiffness of nanosurfaces in the numerical analysis. The computational results reveal that the stress concentration in nanoporous metallic materials is affected by the void geometry and is enhanced by the surface bending stiffness. In addition, the effect of void geometrical parameters on the elastic properties of nanoporous metallic metamaterials with negative Poisson's ratio is studied and the mechanism of surface tensile/bending stiffness is revealed in detail. The results show that the surface bending stiffness increases the effective Young's modulus of nanoarchitected metallic materials with negative Poisson's ratio and randomly distributed nanopores. Abstract : A finite element method considering surface bending stiffness is developed to capture the mechanical behavior of architected nanoporous metallic materials. It is found that the radial stress on the void surface depends on the surface bending stiffness. The surface bending stiffness increases the stress concentration and effective Young's modulus of the materials.